STUDI EMPIRIS TERHADAP FAKTOR PENENTU KEBIJAKAN JUMLAH DIVIDEN - Michell Suherli; Sofyan S. Harahap (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2004)
This research examines variables which are predicted influencing dividend amount distribution. In general, investor have primarily objective is to increase their wealth by return as dividend or capital gain. On the other hand, the company expects continous growth and its going concern, also increase its stockholder's wealth. Fac-tors that predicted influencing dividend distribution amount in this research are fo-cused on 7 factors: liquidity, firm size, capital structure, company's growth, stock price, number of stockholders, and family leadership in Board of Director. This re-search examine financial statement of 85 companies are listed at Jakarta Stock Exchange for period ended December 31, 1998 until December 31, 2001.This result concluded that liquidity and firm size significant influence to divi-dend distribution amount policy, while the other factors: capital structure, company's growth, stock price, number, of stockholder, and family leadership in Board of Direc-tor do not.Keywords: Dividend, Cash, Firm Size, Capital Structure, Growth, Stock Price, Investment